The Personality Analysis of the Steady and Stable Educators in MAN 1 Medan - Nurkholidah, Nurkholidah; Lubis, Saiful Akhyar; Nahar, Syamsu (Budapest International Research and Critics University, 2021)
This study aims to describe the steady and stable personality of educators in MAN 1 Medan. This research is a field research and the research approach used is a descriptive qualitative research approach. In this study, the research background chosen was personality competence in MAN I Medan. Personality competency research focuses on a stable and stable personality. The background of this research is natural. To obtain valid data on the topic being researched, observation, interviews, and documentation are used. The credibility or validity of the data in this study uses triangulation techniques. The triangulation technique in this study used source triangulation and technique triangulation as a way to determine the credibility of the data. The results showed that educators at Madrasah Aliyah Negeri 1 Medan had steady and stable personalities, as evidenced by their respect for differences in ethnicity, gender, responsibility for their duties, pride in being teachers, and continuous self-development, close to God, work ethic. Based on the intention of ukhrawi not solely to be enjoyed, educators act in accordance with religious, legal, social and cultural norms. It is proven that educators at Madrasah Aliyah Negeri 1 Medan carry out the principles contained in the Pancasila ideology as a basis for acting and thinking for all Indonesian citizens with a sense of unity and unity.